Research on malicious behavior detection based on iOS system - Yuliang WANG; Xiaodong CHEN; Tun WU (Dianxin kexue)
Firstly,the cases of malicious application of multiple iOS platforms were enumerated.The main malicious behavior of mobile application under iOS platform was analyzed by dissecting the misuse of crime and the bad influence.The key technologies of malicious behavior detection process were studied.The iOS application malicious behavior detection model was put forward.Finally,iOS application malicious behavior detection solution was given.